2021
DOI: 10.3390/pharmaceutics13101540
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Half-Sandwich Ru, Rh and Ir Complexes with Chrysin Derived Ligands: Strong Effect of the Side Chain in the Ligand and Influence of the Metal

Abstract: An important challenge in the field of anticancer chemotherapy is the search for new species to overcome the resistance of standard drugs. An interesting approach is to link bioactive ligands to metal fragments. In this work, we have synthesized a set of p-cymene-Ru or cyclopentadienyl-M (M = Rh, Ir) complexes with four chrysin-derived pro-ligands with different -OR substituents at position 7 of ring A. The introduction of a piperidine ring on chrysin led to the highly cytotoxic pro-ligand HL4 and its metal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 140 publications
1
6
0
Order By: Relevance
“…Metal complexes are an important class of compounds in anticancer drug development owing to their unique physical, chemical, and structural characteristics and biological activities. Serious side effects of platinum drugs have led to the investigation of other transition-metal complexes, such as ruthenium, rhodium, and palladium complexes. Compared with the typical square-planar Pt­(II) complexes, Rh­(III) complexes show more structural diversity, high cellular uptake, strong antiproliferative activity, and positive tolerance in normal cells. , The rhodium­(III) centers are traditionally considered inactive, but recent studies have shown that the reactivity to biological targets could be enhanced by coordinating appropriate ligands .…”
Section: Introductionmentioning
confidence: 99%
“…Metal complexes are an important class of compounds in anticancer drug development owing to their unique physical, chemical, and structural characteristics and biological activities. Serious side effects of platinum drugs have led to the investigation of other transition-metal complexes, such as ruthenium, rhodium, and palladium complexes. Compared with the typical square-planar Pt­(II) complexes, Rh­(III) complexes show more structural diversity, high cellular uptake, strong antiproliferative activity, and positive tolerance in normal cells. , The rhodium­(III) centers are traditionally considered inactive, but recent studies have shown that the reactivity to biological targets could be enhanced by coordinating appropriate ligands .…”
Section: Introductionmentioning
confidence: 99%
“…Cancer has been a common disease with high incidence, which is widely perceived as one of the leading reasons of death. , Although a series of platinum antitumor drugs such as cisplatin and its derivatives have been applied in clinical practice, the serious side effects have made scientists commit themselves to searching for more efficient and less toxic antitumor drugs. The tumor-killing agents of a number of platinum family metals with reduced side effects and excellent anticancer activity have been widely concerned. The ruthenium complexes NAMI-A and KP1019 have shown the most promising results in preclinical and clinical trials. , Recently, the organometallic platinum group metal compounds offer rich versatility for the rational design of anticancer complexes. According to the structure type, these platinum group metal-based anticancer complexes can be divided into two main groups: cyclometalated complexes and half-sandwich complexes (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the successful introduction of cisplatin 1 as an anticancer drug in the 1980s, interest in the field of bioorganometallic chemistry has rapidly increased and new metal agents in addition to platinum have been investigated as antitumor agents. 2 Among the various transition metal complexes that have been investigated, ruthenium complexes have emerged as promising alternatives to platinum-based drugs, with three ruthenium( iii ) compounds, NAMI-A, NKP-1339, and TLD-1433 having proceeded to phase I clinical trials and two piano-stool Ru( ii ) arene complexes RM175 and RAPTA-C currently in preclinical studies. 3–5 Investigations into their mechanism of action revealed that the anticancer properties of these Ru( iii ) and Ru( ii ) complexes are largely the result of metal–DNA/biomolecule non-covalent interactions such as aromatic π-stacking and C–H⋯π interactions involving the aromatic moieties on these drugs and biomolecules.…”
Section: Introductionmentioning
confidence: 99%